2013
DOI: 10.1158/1535-7163.mct-12-0841
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induces Differentiation Markers Expression in Anaplastic Thyroid Carcinoma via Activation of Notch1 Signaling and Suppresses Cell Growth

Abstract: Anaplastic thyroid carcinoma (ATC) is an extremely aggressive malignancy with undifferentiated features, for which conventional treatments, including radioactive iodine ablation, are usually not effective. Recent evidence suggests that the Notch1 pathway is important in the regulation of thyroid cancer cell growth and expression of thyrocyte differentiation markers. However, drug development targeting Notch1 signaling in ATC remains largely underexplored. Previously, we have identified resveratrol out of over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 46 publications
3
86
1
2
Order By: Relevance
“…Emerging cancer studies have suggested that RSV can antagonize cell growth through activation of intracellular Notch-1. 35,36 In contrast, our study indicates that inhibitory effects of RSV on serum-induced cell proliferation and migration mainly through inactivation of Notch pathway. Furthermore, blockade on Notch-1 intracellular domain release is the most important target.…”
Section: Discussionmentioning
confidence: 53%
“…Emerging cancer studies have suggested that RSV can antagonize cell growth through activation of intracellular Notch-1. 35,36 In contrast, our study indicates that inhibitory effects of RSV on serum-induced cell proliferation and migration mainly through inactivation of Notch pathway. Furthermore, blockade on Notch-1 intracellular domain release is the most important target.…”
Section: Discussionmentioning
confidence: 53%
“…To quantify apoptosis, cells (2×10 5 ) were treated with media or 0.2, 0.5, or 1 µg/ml doxycycline for 96 hours and harvested using non-enzymatic cell dissociation solution, Cellstripper (Cellgro). Both floating and adherent cells were collected, stained with PE Annexin V and 7 AAD fluorescein solutions (BD Pharmingen) for 15 minutes at room temperature in the dark, and flow cytometry was performed as described previously (27). Data was analyzed using FlowJo V5.0 (Tree Star, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the novel Notch1 activator, chrysin, inhibits tumor growth in ATC both in vitro and in vivo (Yu et al 2013a). Resveratrol inhibits cell growth and enhances redifferentiation in ATC cells, dependent upon the activation of Notch1 signaling (Yu et al 2013b). It has recently been shown that Notch signaling is activated in endothelial cells, promoting angiogenesis after interaction with cancer cells in head and neck squamous cell carcinomas.…”
Section: Notch Pathwaymentioning
confidence: 99%